Ultrasound‐assisted synthesis of nanoemulsion/protein blend for packaging application. Issue 5 (11th March 2022) - Benimana, Fidele; Potoroko, Irina Y.; Pathak, Prateek; Sonawane, Shirish H.; Sonawane, Shriram; Bagale, Uday D.
Abstract: In the present work, we studied the formation of sunflower oil nanoemulsion using ultrasound techniques. Later, we investigated the development of active films based on a mixture of whey protein containing sunflower oil base nanoemulsion with different concentrations (10, 25, and 50% of total whey protein). The prepared film was by analyzing using the Fourier transform infrared (FTIR), X‐ray diffraction (XRD), and field‐emission scanning electron microscope (FE‐SEM). The film shows no changes in its integrity and crystallinity compared to the virgin film. The presence of nanoemulsion improves the mechanical properties from 2.75 MPa to 3.52 MPa while it decreases the water vapor permeability from 3.4 × 10 –10 to 1.3 × 10 −10 g/m.s.Pa for concentrations NE (50% of Whey protein). The antioxidant activity for Tween 20 nanoemulsion is 38.7% compared to 36.1% for Tween 80 nanoemulsion. The antimicrobial activity of the film contains sunflower nanoemulsion higher than virgin films. The results showed the potential of blend film of whey protein with nanoemulsion for active films for novel food protection. Abstract : Current research is applicable to protect the food base on packaging material preparation and its characterization in terms of chemical and mechanical properties.